2009
DOI: 10.1093/ndt/gfp521
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerulosclerosis in idiopathic membranous glomerulonephritis: a clinico-pathological and stereological study

Abstract: The present study is probably the first systematic analysis of stereologic parameters in renal biopsies of IMGN with FSGS. Our results objectively demonstrate the glomerular enlargement in the non-sclerosed glomeruli in cases of IMGN with FSGS. This detection of enlarged glomeruli may serve to alert the renal pathologist to the possibility of coexisting FSGS, which is a poor prognostic factor in IMGN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 10 publications
5
26
1
Order By: Relevance
“…The evaluation of FSGS as a predictor factor of renal function outcome has gained much interest but results remain conflicting, with some investigators supporting a pathogenic role of FSGS in declining renal function, providing FSGS and the severity of tubulointerstitial fibrosis as the only independent factors of disease outcome, while others doubt that there is any correlation of FSGS with renal function outcome …”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of FSGS as a predictor factor of renal function outcome has gained much interest but results remain conflicting, with some investigators supporting a pathogenic role of FSGS in declining renal function, providing FSGS and the severity of tubulointerstitial fibrosis as the only independent factors of disease outcome, while others doubt that there is any correlation of FSGS with renal function outcome …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested various histopathologic features on renal biopsy at diagnosis to be associated with a worse renal outcome [4,5,6,7,8,9,10,11,12]. Histopathologic findings that have been reported as meaningful predictors of outcome in i-MN include glomerular scarring and severity of tubulointerstitial disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although smaller studies have suggested that several histopathologic features are associated with worse outcomes in i-MN [4,5,6,7,8,9,10,11,12], a large, collaborative study from Toronto found that pathology did not influence outcomes [13]. The literature contains similar discrepancies regarding the prognostic importance of clinical and laboratory parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Segmental glomerulosclerosis can be seen in other glomerular diseases, including IgA nephropathy, with primarily mesangial pathology 20 and in membranous nephropathy, although this may reflect post-adaptive FSGS. 21 Barisoni et al have proposed a broad definition that makes room under the FSGS tent for segmental glomerulosclerosis with GLA mutations (Fabry disease) and COL4 mutations (Alport syndrome). 22 ADM9 spectrum mutations would then fit within the subcategory of genetic FSGS, the common feature of these diseases being podocyte injury that stems from the mutation.…”
mentioning
confidence: 99%